2007
DOI: 10.1038/sj.emboj.7601576
|View full text |Cite
|
Sign up to set email alerts
|

A Hip1R–cortactin complex negatively regulates actin assembly associated with endocytosis

Abstract: Actin polymerization plays a critical role in clathrinmediated endocytosis in many cell types, but how polymerization is regulated is not known. Hip1R may negatively regulate actin assembly during endocytosis because its depletion increases actin assembly at endocytic sites. Here, we show that the C-terminal proline-rich domain of Hip1R binds to the SH3 domain of cortactin, a protein that binds to dynamin, actin filaments and the Arp2/3 complex. We demonstrate that Hip1R deleted for the cortactin-binding site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 52 publications
6
89
0
Order By: Relevance
“…Hip1R negatively regulates cortactin-stimulated actin polymerization to guarantee a transient and productive interaction between coated pits and actin during vesicle internalization (Engqvist-Goldstein et al, 2004;Le Clainche et al, 2007). In fact, this same proposal could be formulated in our study on CaM/cortactin and vesicles formation in endosomes.…”
Section: Molecular Machinery Involved In the Formation Of The Actin Csupporting
confidence: 51%
See 1 more Smart Citation
“…Hip1R negatively regulates cortactin-stimulated actin polymerization to guarantee a transient and productive interaction between coated pits and actin during vesicle internalization (Engqvist-Goldstein et al, 2004;Le Clainche et al, 2007). In fact, this same proposal could be formulated in our study on CaM/cortactin and vesicles formation in endosomes.…”
Section: Molecular Machinery Involved In the Formation Of The Actin Csupporting
confidence: 51%
“…In trafficking events, cortactin has been involved in clathrin-mediated endocyto-sis as well as in pinocytosis, regulation of epidermal growth factor receptor (EGFR) degradation, or endosomal positioning (McNiven et al, 2000;Cao et al, 2003Cao et al, , 2005Lynch et al, 2003;Cabezas et al, 2005;Merrifield et al, 2005;Sauvonnet et al, 2005;Timpson et al, 2005;Zhu et al, 2005;Mettlen et al, 2006;Le Clainche et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Less is known about the mammalian ortholog of Sla2p, the Huntingtin-interacting protein-1-related protein (Hip1R). However, it has been shown to bind F-actin, to associate with clathrin-coated vesicles, and to form a complex with cortactin, which acts as a negative regulator of actin polymerization in HeLa cells, suggesting that Hip1R may compensate for the absence of mAbp1 during chemotactic migration (64). Growing evidence supports the concept that mechanical force may be required for the development of adhesion sites by inducing recruitment of additional proteins.…”
Section: And Mabp1mentioning
confidence: 79%
“…On the other hand, the subcellular distribution of GFP-HIP1r was found to be unique during specific phases of the cell cycle. During interphase, GFP-HIP1r in HeLa cells was found to be associated with clathrin-coated vesicles as previously described (12,13). In metaphase, the fluorescence signal was found to be concentrated to mitotic spindle fibers, as judged by immunostaining of α-tubulin (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…Several previous reports have shown that these proteins primarily regulate the formation of clathrincoated vesicles and trafficking by associating with actin at the plasma membrane (12,13). However, it was unexpectedly found that embryonic fibroblasts derived from either HIP1 or HIP1r single knockout mice do not have any endocytic defects (3,14,15).…”
Section: Introductionmentioning
confidence: 87%